Proceedings of the 2015 International Conference on Engineering Management, Engineering Education and Information Technology 2015
DOI: 10.2991/emeeit-15.2015.81
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Non-financial Factors on Credit Level: An Empirical Study of Supply Chain Finance Based on E-commerce Platform

Abstract: Abstract. With the development of Internet finance, the traditional supply chain finance is being extended to financial service based on e-commerce. In this condition, except for the financial data that traditional credit evaluation focuses on, non-financial factors based on the Internet and e-commerce platform should also be considered. This paper adopted empirical research method, building the structure equation model to verify some key non-financial factors which influenced supply chain finance credit level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…They concluded that information sharing, external collaboration, digitization and financial institutions are the factors that positively impact SC effectiveness. Fang et al. (2015), through their study of credit levels, enlisted a few nonfinancial factors of credit finance, but the study was confined to e-commerce platforms only.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…They concluded that information sharing, external collaboration, digitization and financial institutions are the factors that positively impact SC effectiveness. Fang et al. (2015), through their study of credit levels, enlisted a few nonfinancial factors of credit finance, but the study was confined to e-commerce platforms only.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2020) studied SC collaborative factors, Nguema et al. (2021) studied the impact of SCF on SC effectiveness; Fang et al. (2015) and Xiao et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…erefore, electronic credit is combined into the credit rating process of the OL-SCF, acting as a reliable complement to creditworthiness of online SMEs [3,22]. e newly added rating indicators may include online exchange history (e.g., registration time), activity level (e.g., trading frequency and transaction amount), interaction intensity with partners (e.g., locations in the trading networks and supply chain stickiness), and customer satisfaction (e.g., online review) [3,[22][23][24]. Since such information is generally privately possessed by B2B platforms, it is a common practice that banks and B2B platforms work together as service providers in the OL-SCF business.…”
Section: Research On Online Supply Chain Finance (Ol-scf)mentioning
confidence: 99%